PC.64 Audit of the Management and follow up of infants who received Therapeutic Hypothermia for Neonatal Encephalopathy in NHS Greater Glasgow and Clyde (GG&C) from January 2008 to December 2010. (9th June 2014) - Smee, N; Moss, H; Gibson, J; Jackson, L
Abstract : Introduction: Neonatal hypoxic-ischaemic encephalopathy (HIE) is the most common cause of long term neurological deficit in term and near-term infants. Controlled hypothermia has been available within tertiary level Neonatal Units in NHS GGC from the time of the seminal UK randomised controlled trial of cooling 1 and is now the standard of care as endorsed by the National Institute for Heath and Clinical Excellence in 2010. 2 Aims: To compare 'cooling' service provision in NHS GGC against local and national standards for initial inpatient management over a three year time period (01/01/2008 to 31/12/2010). Initial management and follow up of these high-risk infants was then evaluated at up to 24 month of age. Results: The clinical care of the infants receiving cooling for HIE within NHS GGC was consistent with local and national standards. However, the level of documentation was substandard when compared to local guidelines. Inconsistencies were identified in relation to neurodevelopmental follow-up. Only 19% of infants had documentation of optimal follow up (to 24 months) from neonatal services. The reasons for this were multifactorial. Recommendations: All neonatal units in GG&C should utilise the now standard neonatal Badger computer system for data recording to optimise documentation during therapeutic hypothermia. To ensure equity of care a standardised pathway of follow up should be established which includes the provision of detailed neurodevelopmental assessment at 24 months of age, regardless of input by other medical specialities or level of concern about disability. References: Azzopardi D, Strohm B, Edwards A, Dyet L, Halliday H, Juszczak E, Kapellou O, Levene M, Marlow N, Porter E, Thoresen M, Whitelaw A, Brocklehurst P. Moderate hypothermia to treat perinatal asphyxial encephalopathy. N Engl J Med . 2009;361:1349–1358 NICE IPG374: Therapeutic hypothermia with intracorporeal temperature monitoring for hypoxic perinatal brain injury: guidance. Issued May 2010